Analisis Strategi UMKM dalam Pengembangan Ekonomi Kreatif pada Industri Kecil Dodol di Kampung Muara Tapus Kecamatan Sungai Aur - Nini Azelvi; Maisarah Leli; Yossi Eriawati (Universitas 17 Agustus 1945 Semarang, 2024)
This paper discusses the Analysis of MSME Strategy in the Development of Creative Economy in the Small Dodol Industry in Muara Tapus Village, Sungai Aur District. The purpose of this study is to analyze what strategies have been implemented by MSMEs based on the creative economy in the small dodol industry in Muara Tapus Village, Sungai Aur District and to provide alternative strategies that are in accordance with the current position and condition of the business. This type of research uses qualitative research with a descriptive approach. The data source used is the primary data source, namely data from informants. The data collection techniques used are observation, interviews and documentation in the small dodol industry in Muara Tapus Village, Sungai Aur District. The subjects in this study were small dodol industry business actors in Muara Tapus Village, Sungai Aur District. Based on the results of the study, it shows that there are several obstacles or constraints on the development of MSMEs, namely minimal capital, human resources, low management. And the strategic factors that influence the development of MSMEs are capital, marketing, operations, human resources and aspects of government policy.